Konsep Pendidikan Islam di Era Abad 21: Tantangan dan Strateginya - Fitriani, Ely; Syarifah, Anisa Hidayatus (Tasamuh: Jurnal Studi Islam, 2023)
Islamic education in its teaching must be adapted to the times. This paper examines Islamic education in the era of globalization, especially in the 21st century. The research method used in this study is a qualitative research method using a literature approach. The results of this study indicate that Islamic education in the 21st century era presents various challenges that have a major impact on the development of Islamic education. In facing these challenges, strategies that can be implemented include modernizing and transforming human resources, changing the vision and mission and objectives of Islamic education, adjusting curriculum and teaching materials, and introducing Islamic education as a whole and comprehensively to society.